Printable and Flexible Planar Silver Electrodes-Based Resistive Switching Sensory Array - Tian, Xiyue; Luo, Zewei; Fan, Tianyi; Zhang, Jinjie; Chu, Junhao; Wu, Xing (Frontiers in Sensors, 2020)
With the advent of the smart flexible electronic devices age, new research directions have emerged. Among them, the resistive switching (RS) sensor attracts a lot of attention, which converts the change of voltage signals into the change of resistance values. In this work, a planar flexible RS structure based on one-step printable silver electrodes was designed and fabricated to simplify device fabrication. The study paves a way for future all-in-one printable and flexible sensors.